Muscle Weakness - Ali Al Kaissi MD, MSc; Sergey Ryabykh MD; Polina Ochirova MD; Vladimir Kenis MD; Jochen G. Hofstätter MD; Franz Grill MD; Rudolf Ganger MD, PhD; Susanne Gerit Kircher MD, MSc (SAGE Publishing, 2017)
Marked ligamentous hyperlaxity and muscle weakness/wasting associated with awkward gait are the main deficits confused with the diagnosis of myopathy. Seven children (6 boys and 1 girl with an average age of 8 years) were referred to our department because of diverse forms of skeletal abnormalities. No definitive diagnosis was made, and all underwent a series of sophisticated investigations in other institutes in favor of myopathy. We applied our methodology through the clinical and radiographic phenotypes followed by targeted genotypic confirmation. Three children (2 boys and 1 girl) were compatible with the diagnosis of progressive pseudorheumatoid chondrodysplasia. The genetic mutation was correlated with the WISP 3 gene actively expressed by articular chondrocytes and located on chromosome 6. Klinefelter syndrome was the diagnosis in 2 boys. Karyotyping confirmed 47 ,XXY (aneuploidy of Klinefelter syndrome). And 2 boys were finally diagnosed with Morquio syndrome (MPS type IV A) as both showed missense mutations in the N-acetylgalactosamine-sulfate sulfatase gene. Misdiagnosis can lead to the initiation of a long list of sophisticated investigations.